Review of the genus Harnischia Kieffer from China (Diptera, Chironomidae), with description of one new species - Yan, Chun-Cai (Zookeys, 2016)
Abstract. The genus Harnischia Kieffer, 1921 from China is reviewed and one new species, Harnischia parallela Yan & Wang, sp. n., is described and illustrated as adult male. Harnischia okilurida Sasa is recognized as a new synonym of Harnischia longispuria Wang & Zheng. The pupae of Harnischia fuscimana Kieffer and Harnischia curtilamellata Malloch are redescribed from material collected in China, and an unplaced pupa is described. Key to male adults and pupae of known species of Harnischia from China is given.